Connectivity and succession of open structures as a key to sustaining light‐demanding biodiversity in deciduous forests. Issue 12 (1st October 2021) - Kozel, Petr; Sebek, Pavel; Platek, Michal; Benes, Jiri; Zapletal, Michal; Dvorsky, Miroslav; Lanta, Vojtech; Dolezal, Jiri; Bace, Radek; Zbuzek, Borivoj; Cizek, Lukas
Abstract: European forests are facing a rapid decline in light‐demanding biota. This has prompted active interventions to re‐establish and maintain partial habitat openness in protected areas. Managers of protected areas, however, need substantially more scientific evidence to support their decisions on where, when and how to intervene. We investigated the importance of spatial continuity of open forest habitats in different years of succession, using six pairs of experimental clearings established in the formerly open, oak‐dominated forests of the Podyji National Park (Czech Republic). In each pair, one clearing was connected to the forest edge, while the other was isolated in closed forest. We sampled butterflies (74 spp.), moths (435 spp.), saproxylic beetles (465 spp.) and vascular plants (567 spp.) on the 12 clearings during the first 5 years of succession. We then compared species richness, abundance and composition of the four taxa between the two clearing types and along the succession. All studied insect groups were substantially more species rich and more abundant in connected than in isolated clearings. Species composition of plants, moths and butterflies differed between the clearing types. The number of species of all studied taxa generally increased from the first to the second or third year after cutting; species composition of all taxa differed among years. This suggests rapid changes in habitat quality and thus limited time for colonisation by light‐demanding organisms. Synthesis and applications . Our results offer an evidence that spatial connectivity and rapid temporal dynamics are important habitat features for light‐demanding insects. Attempts to create or restore habitats for light‐demanding forest biota should take into account that: (a) Insects benefit from direct connection of new open patches to open habitats or flight corridors such as forest edges. (b) Considering plants, the optimal solution is to connect newly created open forest habitats to existing habitats with established biota of high conservation value. (c) Interventions should be carried out within short time intervals, that is within years rather than decades. (d) A fine mosaic of interconnected, open woodland patches in various successional stages is more beneficial than a single large patch with a single successional stage. Abstract : Our results offer an evidence that spatial connectivity and rapid temporal dynamics are important habitat features for light‐demanding insects. Attempts to create or restore habitats for light‐demanding forest biota should take into account that: (a) Insects benefit from direct connection of new open patches to open habitats or flight corridors such as forest edges. (b) Considering plants, the optimal solution is to connect newly created open forest habitats to existing habitats with established biota of high conservation value. (c) Interventions should be carried out within short time intervals, that is within years rather than decades. (d) A fine mosaic of interconnected, open woodland patches in various successional stages is more beneficial than a single large patch with a single successional stage. Souhrn: V evropských lesích dochází k výraznému úbytku přírodnírozmanitosti vázané na otevřená stanoviště. V chráněných územích je proto třebaobnovit aktivní hospodaření a udržovat lesy prosvětlené. Naše studie přinášíklíčové informace o významu propojenosti prosvětlených ploch a potřebnéfrekvenci zásahů. V doubravách Národního parku Podyjí (Jižní Morava) bylo vytvořenošest dvojic maloplošných pasek. Jedna paseka z každé dvojice byla vždypřipojena k okraji lesa a přilehlé louce, druhá paseka byla izolovaná odotevřených stanovišť pruhem hustého lesa. Na těchto dvanácti pasekách jsmeběhem prvních pěti let sukcese zaznamenali 74 druhů denních a 435 druhů nočníchmotýlů, 465 druhů saproxylických brouků a 567 druhů cévnatých rostlin. Porovnalijsme početnost, druhovou bohatost a druhové složení studovaných skupin mezi oběmatypy pasek a mezi roky sukcese. U všech studovaných skupin hmyzu byl počet druhů i jedinců výrazně vyššína připojených pasekách než na izolovaných. U denních a nočních motýlů a u cévnatýchrostlin se navíc lišilo i druhové složení mezi oběma typy pasek. Počet druhů ve všech sledovaných skupinách rostl dva až tři roky povytvoření pasek, druhové složení společenstev se přitom mezi roky lišilo. Tonaznačuje, že kvalita stanovišť se během rané sukcese rychle mění, a vevýsledku tak světlomilné organismy mají omezený čas na jejich kolonizaci avyužití. Shrnutí . Výsledky studie ukazují, že prostorová propojenost a rychlá dynamikasukcese významně ovlivňují světlomilné lesní organismy. Snahy o obnovustanovišť pro ohrožené světlomilné organismy proto musí brát v úvahu, že:(i) hmyzu prospívá, když jsou nově vzniklé plochy přímo propojeny s jinýmiotevřenými stanovišti nebo letovými koridory, např. s okrajem lesa. (ii) Prorozmanitost cévnatých rostlin je důležité propojovat nově vzniklá stanovištěse stanovišti, kde se již nachází ochranářsky významné druhy. (iii) Zásahyby měly být prováděny v intervalech maximálně několika let, nikolidesetiletí. (iv) Jemnozrnná mozaika propojených otevřených lesních stanovišť vrůzných fázích sukcese má pro zachování přírodní rozmanitosti listnatých lesů většívýznam, než jedna velká plocha stejného věku.